Catalytic Removal of Remazol Brilliant Blue R by Manganese Oxide Octahedral Molecular Sieves and Persulfate - Tepe, Ozlem (Asce-Amer Soc Civil Engineers, 2018)
In this paper, manganese oxide octahedral molecular sieves (OMS-2) as a novel catalyst were used in activation of persulfate (PS) for Remazol Brilliant Blue R (RBBR) dye removal. The dye removal efficiencies of different systems including OMS-2 only, PS only, and OMS-2/PS were evaluated, and complete removal using the OMS-2/PS system was achieved in 30min. It was found that operation parameters such as pH, OMS-2, PS, and RBBR concentrations affected RBBR removal. The OMS-2/PS system exhibited excellent catalytic activity in the pH range of 2.52-8.09. The reaction time decreased with increasing OMS-2 and PS concentrations. Quenching tests using tert-butanol and ethanol suggested that sulfate radicals in the OMS-2/PS system are the dominant reactive species. The RBBR degradation reactions could be well-described by the first-order kinetic model. In the optimized condition, total organic carbon (TOC) removal efficiency was 56.8% after 60min. Ultraviolet-visible (UV-vis) spectra were used to ascertain the OMS-2/PS system. The practical applicability of the OMS-2/PS system was also investigated for simulated wastewater.
Keywords: Catalytic removal; Manganese oxide octahedral molecular sieves (OMS-2); Persulfate; Remazol Brilliant Blue R (RBBR)